MALANG FLOWER CARNIVAL AS LAUNCHING PAD FOR FARIZ HOTEL MALANG - Gian Avila Chandra; Andrea Torres; Jessica A. Zacny; Thalita Aldrianita; Aisah Anugerah Qadri (AIBPM Publisher, 2018)
Fariz is hotel located in a strategic place near airport and culinary spot.Currently the management of Fariz hotel do not think foreign tourist as a target market. Fariz hotel still lacks some resource to do an international promotion. Fariz hotel currently using online application and website to promote their service. Their current customer mainly is tour and travel or a company. Fariz hotel potencies are its strategic location and affordable price. The team suggested a promotion program using Malang Flower Carnival as the theme. The program is a bundle package that use Malang Flower Carnival attractiveness to catch foreign tourist interest. This program is not only promote Fariz hotel but also promote Indonesian culture.Malaysia, China, and Australia are countries which both interested in Indonesian culture and have the most tourist visiting Indonesia. That countries are the main target for this promotion program. Fariz hotel management are agreed to do international marketing as long as the marketing program is makes sense and suitable with the current Fariz hotel situations. The team suggest that Fariz hotel should improve the English of their human resource, focusing their target segment, and participate in promoting Malang Flower Carnival.